Decomposition of N2O at low temperature over Co3O4 prepared by different methods - Inayat, A. (2019)
The activity of Co3O4 prepared by different methods was examined for decomposition of N2O in the presence of 2 oxygen concentration. This N2O gas is also a part of NOx gases and it is also nominated as a greenhouse gas that is a big threat for future environment due to very stable compound and having long life many and more than CO2. It is very difficult to make unstable or decompose N2O compound especially at low temperature. Catalytical decomposition is ultimate way to convert N2O into environmental friendly gases. In the present study, Co3O4 was prepared by different methods and used as a catalyst for this purpose. In the preparation of Co3O4, three different methods were used namely solâgel method (Co3O4-S), calcination method (Co3O4-C), and the co-precipitation method (Co3O4-P). The prepared materials were well characterized by TEM, TGA, XRD, and BET surface techniques. These three different preparation methods of Co3O4 were performed to optimize for N2O decomposition. The experimental results showed that the catalytic activities of Co3O4 strongly depended on the Na/Co molar ratio and pH of an alkaline solution during Co3O4 preparation other than reaction temperature and time parameters. The optimized catalyst 1 NaOH + 1 M NH4OH/Co3O4-P was observed highly active at optimum pH value 9.8 and Na/Co molar ratio 0.0120. The highest activity of this optimized catalyst for N2O decomposition was found 98 at 400Â°C while 95, 89, 78, and 68 were recorded at 350Â°C, 300Â°C, 250Â°C and 200Â°C, respectively. Â© 2019 American Institute of Chemical Engineers Environ Prog, 2019. Â© 2019 American Institute of Chemical Engineers